IDNLearn.com connects you with a community of experts ready to answer your questions. Get comprehensive answers to all your questions from our network of experienced experts.


7 - 3x = -x + 1
Can anyone help


Sagot :

Answer:

Answer:

x=3

Step-by-step explanation:

7−3x=−x+1

Step 1: Simplify both sides of the equation.

7−3x=−x+1

7+−3x=−x+1

−3x+7=−x+1

Step 2: Add x to both sides.

−3x+7+x=−x+1+x

−2x+7=1

Step 3: Subtract 7 from both sides.

−2x+7−7=1−7

−2x=−6

Step 4: Divide both sides by -2.

−2x

−2

=

−6

−2

x=3